Vrednotenje Prešernovih pesmi kot recepcijski problem - Božič, Zoran (Slavistična revija, 2011)
The present paper deals with the evaluation of Prešeren's verse in the context of scool readers. The current trend inthe pedagogy of literature in the criteria for selecting literary texts for high-schoo readers is to consider receptional and literary historical principles. A study of the evaluative measures of three leading specialists in Prešeren in the second half of the twentieth century shows that despite important differencies among them, literary historiand mostly appreciate the formally most complex and most demanding texts from the middle period of Prešeren's Romantic opus. Although students are influenced by the literary historical principle, they prefer Prešeren's formally simpler and less demanding poems, especially those with a plot, easier to comprehend, and yielding a full experience of the work.
Keywords: evaluation; high schools; history of literature; literarna zgodovina; literary history; Prešeren, France, 1800-1849; recepcija; reception; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija; srednje šole; vrednotenje